"I Don't Agree with Giving Cash": A Survey Experiment Examining Support for Public Assistance1. (1st November 2016) - Campbell, Colin; Gaddis, S. Michael
Abstract : Objective: Existing research on support for anti‐poverty programs largely focuses on broad categories of welfare. In this article, we examine variations in support across different public assistance programs. Methods: We use an experimental survey design to examine whether support for public assistance is dependent on the type of aid offered. Results: We find that programs that offer benefits in‐kind are more popular than cash transfers. Moreover, food stamps and child‐care subsidies enjoy more support than housing assistance. Open‐ended survey responses show that when evaluating anti‐poverty programs, respondents adopt one of two perspectives: (1) cash assistance is problematic but other forms of assistance are acceptable or (2) any assistance is problematic. Conclusion: By too narrowly focusing on welfare, social scientists run the risk of developing theories and explanations that may not apply to the much larger part of the safety net that is delivered in‐kind.